Comparative analysis of the usage of free-floating carsharing between Berlin and Calgary. - Schnieder, Maren (My University, 2017)
Die Studienarbeit führt einen internationalen Vergleich von stationsunabhängigen Carsharing-Systemen durch. Dabei wird die Stadt Calgary als sehr autoabhängige Stadt mit der Stadt Berlin als Vertreter einer weniger auto-zentrierten Stadt verglichen. Die Zielstellung ist, Erfolgsfaktoren für die weitere Implementierung von Carsharing in eher autoabhängigen Städten zu identifizieren. Die Studienarbeit skizziert zunächst die strukturellen Unterschiede der beiden Städte. Kern der Untersuchung ist die nachfolgende Auswertung von realen Nutzungsdaten der Anbieter DriveNow und car2go einschließlich der Standorte des Fahrtbeginns und Fahrtende der Buchung. Anhand der Ergebnisse kann deutlich gezeigt werden, wie regulatorische Rahmenbedingungen die Nutzung von Carsharing begünstigen können. Dies kann sogar soweit führen, dass Wirkungen des Parkraummanagements durch Carsharing eingeschränkt werden. Somit zeigt die Studienarbeit deutlich, wie wichtig die Evaluation von verkehrsplanerischen Projekten ist.

The purpose of this paper is to investigate possible reasons, based on economic and city characteristics, for the different usage of free-floating carsharing between a car-dependent city (Calgary) and one non-car-dependent city (Berlin). This paper identifies factors that help a free-floating carsharing system to be successful in a city that scores poorly on commonly known success factors of carsharing. Methods: factors were evaluated, namely, geographic and demographic market characteristics, the available transport systems and the costs and household spending of both cities. A dataset which describes the usage of free-floating carsharing in Berlin and Calgary from August 2016 to November 2016 was analyzed in this study. Conclusion: Given the focus of the departures and arrivals in Calgary in areas where parking fees are charged, active parking management could be a success factor for free-floating carsharing in car-dependent cities. However, it is not advisable to solely enforce parking fees within select parts of the home area as individuals generally prefer to use the less expensive mode of transport; which is free-floating carsharing to travel from and to areas with active parking management and their own car for any other trip. As a result, the city would not gain the benefits free-floating carsharing could provide. Recommendations: Based on the results of this study, it is advisable to investigate whether home area wide or city wide parking management and surcharges for trips to downtown could encourage Calgary's members in to use the car2go in a way that it provides the most benefits from a city perspective.
Keywords: Verkehr; Autoverkehr; Carsharing; Städtevergleich; Internationaler Vergleich; Datenauswertung; Parkraummanagement